The ultimate socialite - a satirical commentary on the reliance of social media to interact in the digital age. - Thng, Tracy Wan Ying. (2013)
This project aims to investigate the role in which graphic design can provoke thinking about the use of social media to interact in the digital age. As technology gets more accessible in developed countries in Singapore, we find ourselves interacting less physically and more on social platforms.